High-density Particleboard Made from Agro-industrial Waste and Different Adhesives - Sugahara, Estefani S. [UNESP]; Silva, Sergio A. M. da [UNESP]; Buzo, Ana Laura S. C. [UNESP]; Campos, Cristiane I. de [UNESP]; Morales, Elen A. M. [UNESP]; Ferreira, Bruno S. [UNESP]; Azambuja, Maximiliano dos A. [UNESP]; Lahr, Francisco A. R.; Christoforo, Andre L. (North Carolina State Univ Dept Wood & Paper Sci, 2019)
Particleboards were made using particles from sugarcane bagasse and eucalyptus residues of the pulp industry. The particleboard properties were evaluated according to ABNT NBR 14810-1 (2013), ABNT NBR 14810-2 (2013), and ANSI A208.1 (1999) standards, which compared the efficiency of castor oil-based polyurethane resin (PU-Castor) and urea-formaldehyde resin (UF). The particleboards were composed of 60% wood particles and 40% bagasse, with a 10% adhesive dose based on the dry mass of particles. The following parameters were evaluated: apparent density, moisture content (MC), thickness swelling after 24 h, modulus of rupture (MOR), modulus of elasticity to static bending (MOE), and internal bond strength of panels (IB). The results obtained demonstrated the potential use of eucalyptus and sugarcane bagasse residues in the production of high-density particleboards. The panels produced with PU-Castor showed greater efficiency, and their physical and mechanical properties were compatible with the requirements of the Brazilian standard for P4 panels (structural panels for use in dry conditions) and the American standard for H-3 panels (high industrial density).
Keywords: Particleboards; Castor oil-based polyurethane adhesive; Material recycling; Eucalyptus; Sugarcane bagasse